A Generic Review of Messenger Application: Wechat And Whatsapp - Anak Apon, Ewiena Bivie; Mohd Foozy, Cik Feresa; Shamala, Palaniappan (SOTVI, 2019)
Over the Internet today, communication environment is more easy and interesting to the citizen. There are much interesting in modern technology when they provided a good substrate for creating large-scale data sharing, content distribution, and application-level multicast applications. The important objective of this article is getting information about comparison of two distributed system in messenger application. Messenger application is known as a tool communication that can get any information. The distributed system is one of the independent and single coherent systems it was built an application that will be informed that section is being fixed or replaces to serve more applications or users. The distributed system for this article about the comparison of two distributed system in messenger application for WeChat and Whatsapp, it is also known as the famous application for this generations nowadays.